Analisis Keputusan Memilih Bermain I ZONE di Tebing Tinggi Ditinjau Dari Harga dan Promosi - Fitrianingsih Fitrianingsih; Zulpianda Nublah; Devy Mawarnie Puspitasari (Digital Business Progress, 2023)
The aim of this research are to analyze the effect of priceand promotion on the decision to choose.This research is quatitative with a research sample of 96 parents of consumers who choose to play at I Zone. Collecting data using a questionnaire with data analysis using SPSS. The results of the anakysis show that the price has no significant effect on the decision to choose, promotion has significant effect on the decision to choose, and the price and promotion simultaneously have a significant effect  on the decision to choose.